Enhanced tumor uptake, biodistribution and pharmacokinetics of etoposide loaded nanoparticles in Dalton's lymphoma tumor bearing mice - Movva Snehalatha; Venugopal Kolachina; Ranendra Narayan Saha; Anil Kumar Babbar; Navneet Sharma; Rakesh Kumar Sharma (Wolters Kluwer Medknow Publications, 2013)
Background: Nanotechnology plays a remarkable role in the field of the treatment of Lymphomas associated with tumor. Objective: The purpose of this study is to determine and to compare the tumor uptake, biodistribution and pharmacokinetics of radiolabeled etoposide and etoposide loaded nanoparticles in Dalton's Lymphoma tumor bearing mice and healthy mice. Materials and Methods: Etoposide loaded nanoparticles were prepared by nanoprecipitation technique using the poly (lactic-co-glycolic) acid (PLGA) in the presence of Pluronic F 68 (F 68) as a stabilizer and characterized by particle size analyzer, zeta potential and transmission electron microscope. Etoposide and etoposide loaded nanoparticles were labeled with Technetium-99m (Tc-99m) by the direct method and various quality control tests were carried out. The labeling parameters like labeling efficiency, stability, etc., were optimized to get high labeling efficiency as well as stability of the labeled formulations. Tc-99m labeled formulations were administered intravenously in Balb C mice and their biodistribution and pharmacokinetics were determined. Results: Mean size of the etoposide loaded PLGA nanoparticles was found to be 105.1 nm. The concentration of both free etoposide and nanoparticles increased with time and showed higher tumor concentrations of both free etoposide and nanoparticles increased with time and showed higher retention, indicating their applicability in effective and prolonged tumor therapy. Nuclear scintigraphic images confirm the presence of labeled complexes at the site of tumor for 24 h at higher concentration than in the normal muscles. Conclusion: This study indicated higher tumor affinity and targeting properties of etoposide loaded nanoparticles than free etoposide.